(untitled) - Meléndrez A., Ronald D.

Evaluation of the Antibacterial and Antifungal Activity of Isolated Bacteria from Appenzeller® Swiss Cheese (Zamorano: Escuela Agrícola Panamericana, 2020, 2020)
Pathogenic bacteria are etiological agents that cause diseases related to food consumption, and spoilage microorganisms convert foods in unacceptable for consumers. In dairy products, there exist groups of microorganisms like bacteria, yeast, and molds. These bacteria can be isolated from dairy products like Appenzeller® Swiss cheese. The bacteria can inhibit other types of pathogenic and spoilage microorganisms that can increase the shelf-life of the products. The research study assessed the antimicrobial activity of isolated bacteria from Appenzeller® Swiss Cheese and identified the strains. Phase 1: Isolation of the bacteria where 27 morphological different strains were found. Phase 2: Characterization of the strains, discovering that Bacillus like the principal genus and Staphylococcus. Phase 3: Evaluation of the antimicrobial activity presented by six different strains, four only with inhibition activity against Aspergillus fumigatus, one with inhibition against Bacillus amyloliquefaciens and Aspergillus fumigatus, and the last one with inhibition of Listeria innocua, and the other two microorganisms evaluated. The antagonistic effect could be attributed to chitinase, protease, and volatile organic compounds production as butan-1-ol and 3-methylbutan-1-ol. The further applications for the isolated bacteria can be tested on Aspergillus and Penicillium that affect the cheese industry, B. stearothermophilus, and B. coagulans that produce the flat sour flavors, and Aspergillus genera with potential mycotoxin production. Further studies need to evaluate metabolite characterization and extend the spectrum of microorganisms evaluated.